Biases in the effects of family background characteristics on voting preference: the Dutch case - de Vries, J; de Graaf, N; Eisinga, R (Elsevier, 2009)
This article examines whether intergenerational transmission of party preference is biased by retrospective and other-report measurement of family background characteristics. [In our model the dependent variable is voting preference, while one of our explanatory variables is father's party preference. Therefore we speak of the intergenerational transmission of party preference.]. In addition the consequences of measurement error for the effects of father's church membership, his church attendance, whether he is self-employed, educational attainment, church membership, church attendance, whether the respondent is self-employed, and occupational status on voting preferences are investigated. It turns out that the effects of educational attainment and father's party preference are underestimated if measurement error is not taken into account. The role of correlated error is negligible. As the effect of father's party preference is substantial and becomes even stronger after correcting for measurement error, it is advisable to include it in the model, while inputing information on measurement error.